2017
DOI: 10.1038/mp.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Next-gen sequencing identifies non-coding variation disrupting miRNA-binding sites in neurological disorders

Abstract: Understanding the genetic factors underlying neurodevelopmental and neuropsychiatric disorders is a major challenge given their prevalence and potential severity for quality of life. While large scale genomic screens have made major advances in this area, for many disorders the genetic underpinnings are complex and poorly understood. To date the field has focused predominantly on protein coding variation, but given the importance of tightly controlled gene expression for normal brain development and disorder, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 65 publications
0
61
0
Order By: Relevance
“…However, further functional assays must be conducted to shed mechanistic light on the pathways involved. There is growing evidence that noncoding regions of the genome have an impact on reading-related traits, and the identification of a lncRNA associated with a reading endophenotype lends additional support (59). Implication of RNLS also reinforces the hypothesis that alterations in neurochemical modulation in the brain could contribute to impairments in reading performance.…”
Section: Discussionmentioning
confidence: 84%
“…However, further functional assays must be conducted to shed mechanistic light on the pathways involved. There is growing evidence that noncoding regions of the genome have an impact on reading-related traits, and the identification of a lncRNA associated with a reading endophenotype lends additional support (59). Implication of RNLS also reinforces the hypothesis that alterations in neurochemical modulation in the brain could contribute to impairments in reading performance.…”
Section: Discussionmentioning
confidence: 84%
“…Recent genome sequencing studies have identified many risk genes from the loss-of-function protein-coding variants, which has driven a move toward analysis of convergent risk pathways [1][2][3][4]. However, less is known about the contribution to risk by the variants in non-coding regulatory regions, which hold the potential to disrupt the finely tuned biological pathways involved in brain development, as demonstrated by a recent study in the influence of the 3′ untranslated regions (3′UTR)-regulatory variants in language impairment [5]. Nevertheless, progress is being made by using whole-genome sequencing of the ASD families.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these novel approaches involve predicting whether a variant has the potential to change the dynamics of gene networks by disrupting the interactions between key regulatory molecules, such as miRNAs and transcription factors, and their target functional pathways [8,15,16]. There is now an increased focus on ASD-associated mutations within the regulatory regions, particularly near-known ASD-risk genes [17,18], with studies examining the enhancer regions [19] and microRNA targeting [5]. Together these data provide a vision of how we might assess the potential impact of non-coding regulatory DNA variations associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we used reporter assays 104,105 to determine if the bat and human versions of miR-337-3p were functionally active and if they showed species-specific regulation of an “ideal” predicted target sequence (Table S20). While bat miR-337-3p strongly repressed the expression of its cognate bat target sequence, it had no effect on the human site, and vice versa (Fig.…”
Section: Introductionmentioning
confidence: 99%